ISO/IEC/IEEE International Standard - Systems and Software Engineering-- Life Cycle Management-- Part 2: Guidelines for the Application of ISO/IEC/IEEE 15288 (System Life Cycle Processes) (ISO/IEC/IEEE 24748-2:2018(E), 2018)
This document specifies requirements and procedures for managing information for users throughout the software-, services-, and systems-development life cycle. It applies to people or organizations producing suites of information, to those undertaking a single information-development project, and to information produced internally, as well as to information contracted to outside service organizations. It provides details of the information-development and project-management processes and also presents aspects of strategic planning and translation management that managers apply. It covers management activities related to starting a project, building a team, and managing information through the translation and localization process. It addresses productivity and quality measurements needed for management control. This document is independent of the software tools that may be used to produce or manage information for users and applies to both printed, embedded, and mobile information. Much of its guidance is applicable to information for users of systems of hardware as well as software, systems, and services. This document specifies requirements and procedures for managing information for users throughout the software-, services-, and systems-development life cycle. It applies to people or organizations producing suites of information, to those undertaking a single information-development project, and to information produced internally, as well as to information contracted to outside service organizations. It provides details of the information-development and project-management processes and also presents aspects of strategic planning and translation management that managers apply. It covers management activities related to starting a project, building a team, and managing information through the translation and localization process. It addresses productivity and quality measurements needed for management control. This document is independent of the software tools that may be used to produce or manage information for users and applies to both printed, embedded, and mobile information. Much of its guidance is applicable to information for users of systems of hardware as well as software, systems, and services.